2023
DOI: 10.1111/1556-4029.15233
|View full text |Cite
|
Sign up to set email alerts
|

Wrongful convictions and claims of false or misleading forensic evidence

Abstract: The results are reported of a study to examine case factors associated with 732 wrongful convictions classified by the National Registry of Exonerations as being associated with “False or Misleading Forensic Evidence.” A forensic error typology has been developed to provide a structure for the categorization and coding of factors relating to misstatements in forensic science reports; errors of individualization or classification; testimony errors; issues relating to trials and officers of the court; and eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Perhaps the persistence of discrepancy rates throughout history has resulted in the practice of forensic pathologists having inappropriate confidence in experience and individual customary practice [60][61][62]. Such a feature might be a potential source of error in formulating conclusions [4].…”
Section: Apophenic Vs Evidence-based Forensic Medicinementioning
confidence: 99%
“…Perhaps the persistence of discrepancy rates throughout history has resulted in the practice of forensic pathologists having inappropriate confidence in experience and individual customary practice [60][61][62]. Such a feature might be a potential source of error in formulating conclusions [4].…”
Section: Apophenic Vs Evidence-based Forensic Medicinementioning
confidence: 99%
“…Research has identified a significant subset of cases where unvalidated methodologies have been associated with cases of wrongful conviction [ 10 ] and there is acknowledgement that methodologies lacking the underpinnings of analytical validity have led to the discrediting of methods used in evidence under the banner of forensic science (e.g. bite marks) [ 11 , 12 ].…”
Section: Erosion Of Trust In (Forensic) Sciencementioning
confidence: 99%
“…Unawareness of these may lead an expert witness to unknowingly omit disclosures of information to the court that are required of an expert. Whilst there is benefit in legal practitioners themselves having training to understand scientific evidence and engage with the forensic science community, it is ultimately the responsibility of the expert witness to meet their role in assisting the court [ 10 ]. Material omissions in reports or testimony have the potential to open judgements to appeal and leave the expert, and their agency, open to questions as to the strength of their expertise, quality of work and the validity of the forensic information [ 16 ].…”
Section: Erosion Of Trust In (Forensic) Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In forensic psychiatry, where research suggests that juries and judges tend to misinterpret scientific evidence in court, for instance overestimating the reliability of neuroscientific evidence (126), leading to miscarriages of justice (127), the potential introduction of genAI-fabricated evidence introduces the risk of wrongful convictions grounded in maliciously AI-generated scientific evidence.…”
Section: Genai Deepfake Evidence and The Quest For Realitymentioning
confidence: 99%